Refleksi Pembatasan Usia Perkawinan dalam Undang-undang Nomor 1 Tahun 1974 tentang Perkawinan menurut Filsafat Hukum Keluarga Islam - Moch. Nurcholis (INSTITUT AGAMA ISLAM BANI FATTAH (IAIBAFA), 2014)
To realize the ideal family, fulfilling sakînah element, mawaddah and rah?mah is a must, the presence of law No. 1 of 1974 about marriage (UUP) has a significant role in the country predominantly Muslim Indonesia. One form UUP rules for applying the principle of mental and physical readiness is the restriction of a certain age to get married. how UUP set age limits marriage? and what philosophical value if observed with the philosophy of Islamic family law? This research analyzes using descriptive-analytic method with the conclusions; the marriage age restriction as part of efforts for the realization of setting the ideals of marriage as set forth in paragraph (1). Restrictions UUP marriage age still embrace opportunities for UUP exceptions as set out in article 7 paragraph (2). While the philosophical value of these restrictions can be reviewed through the aspects ontological, epistemological and axiological. According to the philosophy of family law, marriage age restriction category as philosophy tashrî’ especially those problems maqâs?id al-ah?kâm in the form of compliance benefit and resist damage.